2021
DOI: 10.1108/ejtd-09-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Empathic organizational culture and leadership: conceptualizing the framework

Abstract: Purpose This paper aims to conceptualize and discuss empathic organizational culture and leadership along with organizational implications. Design/methodology/approach The authors reviewed literature to conceptualize empathic organizational culture and leadership. They referred to Hofstede’s organizational culture concept and studies on empathy to explore how leader–follower relationships are influenced by a leader’s empathic disposition. Findings Organizational leadership is instrumental in shaping employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…The results suggested that leaders' empathic communication mediates the relationship between servant leadership and followers' workplace loneliness, and servant leadership can indirectly ease followers' loneliness experience. This finding further supports the effectiveness of empathy in leadership and the fact that a leader's empathy positively predicts followers' well-being [80].…”
Section: The Mediation Role Of Leaders' Empathic Communicationsupporting
confidence: 70%
See 1 more Smart Citation
“…The results suggested that leaders' empathic communication mediates the relationship between servant leadership and followers' workplace loneliness, and servant leadership can indirectly ease followers' loneliness experience. This finding further supports the effectiveness of empathy in leadership and the fact that a leader's empathy positively predicts followers' well-being [80].…”
Section: The Mediation Role Of Leaders' Empathic Communicationsupporting
confidence: 70%
“…As an interpersonal helping strategy, empathy fosters positive leader-follower relationships and high-quality LMX [80,81]. Followers perceive servant leadership as possessing strong empathy [82], which may explain servant leaders' sensitivity to followers' needs [50].…”
Section: Leader Empathymentioning
confidence: 99%
“…Optimism refers to a positive outlook on the future, while resilience reflects an individual’s ability to bounce back from adversity (Luthans, Avolio, Avey, & Norman, 2007c, Luthans, Avey, Avolio, Norman, & Combs, 2006, Luthans, Avey, & Patera, 2008, Luthans, Youssef, & Avolio, 2007b; Magnano, Craparo, & Paolillo, 2016). PsyCap has been found to have a positive association with favorable attitudes, behaviors, actions, effectiveness and mental and emotional well-being of staff members, as well as a potential conflict with skepticism, intentions to turn over and employee absenteeism (Arghode, Lathan, Alagaraja, Rajaram, & McLean, 2021; Darr & Johns, 2008; Kim, 2019; Riasudeen & Singh, 2021; Tanjung, Syahrizal, & Abror, 2021). Research has also shown that PsyCap is positively related to employee well-being, job satisfaction and work engagement (Luthans et al, 2015; Nair et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this research, it can be concluded that education and training have a positive and significant effect on work motivation (Elliott). Then study conducted by Arghode (2022), based on the research results, concluded that training has a positive and significant effect on work motivation (Arghode 2022).…”
Section: Effect Of Employee Training On Motivationmentioning
confidence: 99%
“…The results of this study also support the results of previous research that leadership influences employee performance (Elqadri 2015). Furthermore, research conducted by Arghode (2022), based on the study results, can be concluded that it influences employee performance (Arghode 2022). Then the research was undertaken by Grossman 2014); based on the study results, it can be concluded that there is a leadership influence on employee performance (Grossman 2014).…”
Section: The Influence Of Leadership On Employee Performancementioning
confidence: 99%